Volume 10: Ocean Renewable Energy 2017
DOI: 10.1115/omae2017-62136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Wave-Powered, Reverse-Osmosis System and its Economic Availability in the United States

Abstract: A wave energy converter (WEC) system has the potential to convert the wave energy resource directly into the high-pressure flow that is needed by the desalination system to permeate saltwater through the reverse-osmosis membrane to generate clean water. In this study, a wave-to-water numerical model was developed to investigate the potential use of a wave-powered desalination system (WPDS) for water production in the United States. The model was developed by coupling a time-domain radiation-and-diffraction-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Yu and Jenne [12] presented a preliminary study on the potential levelized cost of water (LCOW) for California, which showed a similar LCOW as compared to the value estimation for the United Kingdom provided by Folley et al [7]. In the study, the WEC and hydraulic interaction was simulated using a wave-to-water numerical model.…”
Section: Introductionmentioning
confidence: 82%
“…Yu and Jenne [12] presented a preliminary study on the potential levelized cost of water (LCOW) for California, which showed a similar LCOW as compared to the value estimation for the United Kingdom provided by Folley et al [7]. In the study, the WEC and hydraulic interaction was simulated using a wave-to-water numerical model.…”
Section: Introductionmentioning
confidence: 82%
“…There are two primary applications of wave energy converters (WECs) under consideration: converting wave energy to electrical energy and using wave energy to power the desalination of seawater. It has been argued that the application of wave energy to desalination, specifically reverse osmosis (RO) desalination, can be more economical than the production of electrical power [1] and several groups have worked to evaluate and advance the technology for that purpose [2][3][4][5]. The cited advantage of applying wave energy to reverse osmosis comes with the use of a hydraulic power take-off (PTO) with filtered seawater as the working fluid and direct coupling to the RO process; the advantage is that significant power conversion losses are avoided [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Historical data for the occurrence rate of sea conditions near Humboldt Bay, CA, shown in Figure 2, are used to weight average power capture performance across sea conditions, providing estimates for annual average performance. These data were originally generated for [1] using the methods given in [28]. Bench-marking performance results of this study is facilitated by literature that has considered this WEC in design studies [1,3,7] and experimental testing [29], including results assuming the same rates of occurrence for sea conditions [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mainly, studies are based on the use of wind turbines or solar plants, but there are also proposals where other renewable sources, such as sea currents, are used [34]. This application could be interesting particularly for some islands where the scarcity of drinking water is more severe.…”
Section: Introductionmentioning
confidence: 99%